Longer term effectiveness of inpatient multidisciplinary rehabilitation on health-related quality of life in MS patients: a pragmatic randomized controlled trial – The Danish MS Hospitals Rehabilitation Study. (March 2018) - Boesen, Finn; Nørgaard, Michael; Trénel, Philipp; Rasmussen, Peter Vestergaard; Petersen, Thor; Løvendahl, Brita; Sørensen, Jan
Background: There is insufficient evidence to support the effectiveness of multidisciplinary rehabilitation on the health-related quality of life (HRQoL) of MS patients. Objectives: To evaluate the longer term effectiveness of inpatient multidisciplinary rehabilitation on the HRQoL of MS patients. Methods: The study was a two-hospital, pragmatic, randomized controlled trial with a 6-month follow-up. Patients aged 18–65 years with MS and Expanded Disability Status Scale scores ≤7.5 were randomly assigned (1:1) to 4 weeks of inpatient multidisciplinary rehabilitation (20 days of scheduled rehabilitation) or 6 months on a wait list. The outcome measures were Functional Assessment in Multiple Sclerosis (FAMS), Multiple Sclerosis Impact Scale-29 (MSIS-29), EQ-5D-5L and 15D. Results: We randomized 213 patients to the wait-list control group and 214 patients to the treatment group. Trends in favour of the treatment group were observed across all measures. However, the difference was significant in only two of the six measures. The treatment effect was −2.7 (95% CI: −5.6 to (−0.1)), p = 0.046) for the MSIS-29 Psychological and 0.017 (95% CI: 0.005–0.030, p = 0.008) for the 15D. FAMS, which we used to calculate the sample size, was not significant. Conclusion: The results indicated that inpatient multidisciplinary rehabilitation is effective in improving the HRQoL of MS patients after 6 months.